Disruptive behaviour disorders among Northern Sotho speaking children - Madileng, Lerato Dorothea (My University, 2006)
Objective: The objective of this study was two fold: the first being to establish a relationship between the scales of Disruptive Behaviour Disorders rating scale, namely, Inattention, Hyperactivity/Impulsiveness, ODD, and CD. The second objective was to compare Inattention, Hyperactive/Impulsive, ODD and CD symptoms in all the DBD subtypes (ADHD-I, ADHD-H/I, ADHD-C, ODD, CD) and a Non-DBD comparison group. Sample: Both the clinical group and the comparison group were obtained by screening using the Northern Sotho version of the Parent/Teacher Disruptive Behaviour Disorder rating scale (DBD). The sample in this study (N=230) consisted of Northern Sotho speaking primary school children with ages ranging from 7-13. Results: The results of this study showed significant correlations between the scales of the DBD rating scale ranging from strong to weak. The comparison study showed a strong association between symptoms of ADHD and the Aggressive Disorders, especially the ADHD-C group which seemed to be the most affected group with the possibility of developing aggressive symptoms and antisocial behaviour disorders.
Thesis (M. A. (Clinical Psychology)) -- University of Limpopo, 2006
Keywords: Children; Northern Sotho language; Attachment disorder in children; Behavior disorders in children -- South Africa; Attention-deficit hyperactivity disorder; Oppositional defiant disorder in children; Conduct disorders in children